Implementasi Wakalah Pada Surat Kredit Berdokumen Dalam Negeri Di Perbankan Syariah - Sokhikhatul Mawadah; Tria Pibriani (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2022)
Domestic Letter of Credit is a written promise based on the written request of the applicant (Applicant). One of the written promises is that which binds the issuing bank to: Authorize another bank to make payments to the beneficiary and pay the draft drawn by the beneficiary. This research is a qualitative research. The data used are primary data derived from interviews while secondary data obtained from books, journals, and previous research. The results of the study stated that BSI Semarang City not only used wakalah bil ujrah contracts on SKBDN, but also used kafalah and murabahah contracts. BSI gets a fee (ujrah) based on risk. Implementation of Sharia Compliance BSI Semarang City on SKBDN according to maqashid sharia. Maqashid Sharia in question include: 1). Ad-dien: maintaining religion, BSI Semarang City is guided by the Koran, Hadith, and other Islamic laws in carrying out activities. 2). an-nafs: maintaining the soul, the SKBDN service involves several parties. 3). al-aql: maintaining reason, education through seminars and training. 4). an-nasl: maintaining offspring, BSI guarantees that customer funds come from halal funds that have a good impact on families and descendants 5). al-mal: maintain property, BSI takes profit through fees charged.